KEMAMPUAN KOMUNIKASI MATEMATIK SISWA KELAS II SD PADA MATERI MENGKUR BERAT DENGAN MENGGUNAKAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION - Rusmiati Rusmiati; Siti Ruqoyyah (IKIP Siliwangi, 2021)
Mathematical communication is a basic skill that students must master since elementary school. Generally, this mathematical communication skill is still not honed in the field. Many students find it difficult to apply mathematics lessons in the real world and do not yet understand the importance of learning mathematics in everyday life. Realistic Mathematics Education approach is one solution to overcome this problem. Students get a more meaningful learning experience because they are directly related to the real world. The method used in this research is descriptive qualitative method in which the researcher performs an analysis to obtain solutions and conclusions in accordance with the research objectives. The instruments in this study consisted of a written test, observation sheets and an attitude scale questionnaire. The achievements of this study show the expected results. Teachers and students show a positive response to the learning given. Students' mathematical communication skills are better than before learning with the Realistic Mathematics Education approach.